2022
DOI: 10.1111/ajco.13774
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with resistance to initial methotrexate treatment in women with low‐risk gestational trophoblastic neoplasia

Abstract: Aim To compare clinical characteristics and identify factors predictive of resistance to initial treatment with methotrexate‐folinic acid (MTX‐FA) in women with low‐risk gestational trophoblastic neoplasia (GTN). Methods Retrospective chart reviews were conducted in patients diagnosed with low‐risk GTN who were treated with MTX‐FA at Siriraj Hospital between 2002 and 2018. Demographic data, disease characteristics, treatment response, toxicity, and data of the subsequent pregnancy were collected and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…HCG>10 5 IU/l or tumor size>5 cm, the resistance and relapse and toxicity were significantly higher than hCG<10 3 IU/l or tumor size <3 cm. Phianpiset et al [12] , analyzed 113 patients of low-risk GTN and they found that serum hCG≥15 000 IU/l which is an independent factor to predict the failure of treatment by Methotrexate-Folinic Acid (MTX-FA). A study analyzed 365 patients of low-risk GTN, they have considered hCG>300 IU/l increased the failure risk which is an important factor for the treatment by second-line Act-D [13] .…”
Section: According To the Recommendations Of 2021 Nationalmentioning
confidence: 99%
“…HCG>10 5 IU/l or tumor size>5 cm, the resistance and relapse and toxicity were significantly higher than hCG<10 3 IU/l or tumor size <3 cm. Phianpiset et al [12] , analyzed 113 patients of low-risk GTN and they found that serum hCG≥15 000 IU/l which is an independent factor to predict the failure of treatment by Methotrexate-Folinic Acid (MTX-FA). A study analyzed 365 patients of low-risk GTN, they have considered hCG>300 IU/l increased the failure risk which is an important factor for the treatment by second-line Act-D [13] .…”
Section: According To the Recommendations Of 2021 Nationalmentioning
confidence: 99%